Anaemia in Trimester III Pregnant Women Unrelated with LBW Incidence - Dyah Ekowati (Universitas Islam Jember, 2022)
Anaemia is a decrease in red blood cells or hemoglobin so that it is unable to supply oxygen to the tissues. One of the effects of anaemia in pregnancy is LBW. Data at the Bungatan Health Center, namely 29.1% of babies born with LBW. The incidence of LBW should be 7.5% of the IDHS. The aim of the study was to determine the relationship between anaemia in third trimester pregnant women and the incidence of LBW at the Bungatan Health Center, Situbondo Regency. The research design is an analytical survey using a